Algal Bacterial Consortia in Wastewater Treatment for Nutrient Removal and Biomass Production - Miftah Alfeetouri Miftah, (Journal of Libyan Academy Bani Walid, 2025)
Eutrophication from excess nitrogen (N) and phosphorus (P) demands sustainable removal methods. Algal-bacterial consortia (ABC) in reactors can recover these nutrients while producing biomass, using sunlight and CO₂. In this study we designed and ran three pilot systems - a high-rate algal raceway pond (HRAP), a revolving algal biofilm (RAB) reactor, and an algal-bacterial granular sludge sequencing batch reactor (ABGS) - treating municipal wastewater streams. Influent/effluent nutrients (TN, NH₄⁺, NO₃⁻, TP, PO₄³⁻), organics (COD/TOC), and biomass metrics (VSS, chlorophyll-a, lipids, proteins) were measured, along with DO, pH, light, and community composition. Steady-state ABC systems achieved markedly higher nutrient removal than algal-only or bacteria-only controls. For example, consortia removed ~70-90% TN and ~80-95% TP (depending on conditions), versus 40-60% in monocultures. Biomass productivity reached ~10-30 g m⁻² d⁻¹ in outdoor HRAPs and 5-20 g m⁻² d⁻¹ on RABs, with ~15 g m⁻² d⁻¹ typical. Key mechanisms included algal photosynthetic O₂ fueling bacterial nitrification and bacterial CO₂ driving algal growth. In one RAB-microbial fuel cell system, ~96% COD and ~98% NH₄⁺ removal were achieved while generating biomass. Biofilm and granule configurations settled rapidly and were easily harvested, consistent with their high solids content. Community analyses showed convergence toward mixed consortia dominated by heterotrophs (e.g. Proteobacteria) and microalgae (e.g. Chlorella). Overall, ABC processes outperformed single cultures by leveraging O₂-CO₂ exchange and niche complementarity, enabling low-energy nutrient removal and valuable biomass recovery in scalable systems.